The mechanism of transforming diamond nanowires to carbon nanostructures - Sorkin, Anastassia (2014)
The transformation of diamond nanowires (DNWs) with different diameters and geometries upon heating is investigated with density-functional-based tight-binding molecular dynamics. DNWs of 〈100〉 and 〈111〉 oriented cross-section with projected average line density between 7 and 20 atoms Å−1 transform into carbon nanotubes (CNTs) under gradual heating up to 3500–4000 K. DNWs with projected average line density larger than 25 atoms Å−1 transform into double-wall CNTs. The route of transformation into CNTs clearly exhibits three stages, with the intriguing intermediate structural motif of a carbon nanoscroll (CNS). Moreover, the morphology plays an important role in the transformation involving the CNS as one important intermediate motif to form CNTs. When starting with $\langle \bar {2}1 1\rangle $ oriented DNWs with a square cross-section consisting of two {111} facets facing each other, one interesting structure with 'nano-bookshelf' shape emerges: a number of graphene 'shelves' located inside the CNT, bonding to the CNT walls with sp3 hybridized atoms. The nano-bookshelf structures exist in a wide range of temperatures up to 3000 K. The further transformation from nano-bookshelf structures depends on the strength of the joints connecting shelves with CNT walls. Notably, the nano-bookshelf structure can evolve into two end products: one is CNT via the CNS pathway, the other is graphene transformed directly from the nano-bookshelf structure at high temperature. This work sheds light on the microscopic insight of carbon nanostructure formation mechanisms with the featured motifs highlighted in the pathways.